In-house Preparation of Examination Papers using troff, tbl, and eqn. - Brailsford, David F. (Boole Press Ltd, 1984)
Starting in December 1982 the University of Nottingham decided to phototypeset almost all of its examination papers `in house' using the troff, tbl and eqn programs running under UNIX. This tutorial lecture highlights the features of the three programs with particular reference to their strengths and weaknesses in a production environment. The following issues are particularly addressed: